Comparative study of different soil moisture measuring methods - PRAKASH MOHAN M. M; Rajitha K; Sudha P; Er. Shyla Joseph (Guide) (Tavanur 2001 Kelappaji College of Agricultural Engineering and Technology)
Comparative study of different soil moisture measuring methods
Comparative study of different soil moisture measuring methods